Vitamin D, low birthweight preterm and full-term newborns: time for a paradigm shift - I.N. Zakharova; S.V. Mal'tsev; V.V. Zubkov; V.A. Kur'yaninova; A.V. Dmitriev; S.I. Malyavskaya; L.I. Mal'tseva; N.E. Verisokina; L.Ya. Klimov; E.N. Vasil'eva; A.A. Krushel'nitskiy; A.V. Makhaeva; et al. (LCC «Medicine-Inform», 2020)
I.N. Zakharova1, S.V. Mal'tsev1, V.V. Zubkov2, V.A. Kur'yaninova3, A.V. Dmitriev1,4, S.I. Malyavskaya5, L.I. Mal'tseva6, N.E. Verisokina3, L.Ya. Klimov3, E.N. Vasil'eva7, A.A. Krushel'nitskiy1, A.V. Makhaeva1, E.D. Zhdakaeva1, A.L. Zaplatnikov1 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2V.I. Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology, Moscow, Russian Federation 3Stavropol State Medical University, Stavropol, Russian Federation 4Ryazan State Medical University, Ryazan, Russian Federation 5North State Medical University, Arkhangelsk, Russian Federation 6Kazan State Medical Academy - branch of the Russian Medical Academy of Continuous Professional Education, Kazan, Russian Federation 7I.N. Ul'yanov Cheboksary State University, Cheboksary, Russian Federation This article discusses negative effects of vitamin D deficiency on low birthweight preterm and full-term newborns. Results of the studies on vitamin D provision to pregnant women and their newborn children are addressed. Vitamin D deficiency is highly prevalent in pregnant women and newborns. It was demonstrated that inadequate antenatal provision of a fetus with vitamin D may result in congenital rickets and neonatal seizures due to hypocalcemia in newborns and also accounts for increased rates of necrotic enterocolitis, bronchopulmonary dysplasia, and impaired growth and development as well as higher risk of lower respiratory tract infections (i.e., bronchiolitis, pneumonia) during the first year of a child's life. In addition, it was shown that persistent vitamin D deficiency in future years may be associated with recurrent respiratory infections, allergic (e.g., atopic dermatitis, asthma, etc.), autoimmune, endocrine, and psycho-neurological disorders. Prev entive and therapeutic strategies for vitamin D deficiency in low birthweight preterm and full-term newborns since neonatal period are discussed. Keywords: vitamin D, vitamin D deficiency, calcidiol, low birthweight newborn, preterm newborn, full-term newborn. For citation: Zakharova I.N., Mal'tsev S.V., Zubkov V.V. et al. Vitamin D, low birthweight preterm and full-term newborns: time for a paradigm shift. Russian Journal of Woman and Child Health. 2020;3(2):142-148. DOI: 10.32364/2618-8430-2020-3-2-142-148.